Kamasan: Goldsmith Tradisional Sunda - Busratul Mukmin Sjahroeddin; Agus Sachari; Meirina Triharini; Muhammad Ihsan DRSAS (JURNAL RUPA, 2018)
Every culture has its own craft product made by a specialized craftsman. Even so, wider community nowadays in Indonesia do not give attention to traditional craftsman as they should. Many of traditional craftsman has been alienized even perish from their community. One of the traditional craftsmen who has been existing and known in Sundanese people society are kamasan. Kamasan is the name of Sundanese traditional goldsmith who will make jewelry or embed precious metal to other product. Today presence of kamasan almost like a myth, even on Sundanese community. Rapid growth and higher quantity demand of jewely from Sundanese people that cannot be fulfilled by kamasan make them outcast from the mainstream precious metal and jewelry business scene. Beside that, the economic inflation that struck globaly caused many of kamasan changed their profession. In effort to find kamasan that still exist around Bandung, an ethnographical approach was performed in one of the kamasan village at southern Bandung. From those communities finally found only one kamasan who still practicing goldsmith until today. That kamasan persistently practicing goldsmith as known as in Sundanese traditional culture. Traditional craftsmen absence from its community affected the loss of various cultural knowledge. That condition will make a community alienated to their own cultural roots and awareness.